PENGAJARAN VOCAL PLACEMENT DALAM UPAYA MENINGKATAKAN KEMAMPUAN MEMBIDIK NADA PADA ANAK USIA 5-8 TAHUN - Cindy Angelina Sambite; Yohanes Dwi Pramono Mahardiko (Universitas Kristen Immanuel, 2024)
Teaching vocal placement is a crucial aspect in developing the ability of children aged 5-8 years to identify and produce notes correctly. The research uses learning strategies theat are centered correte and interactive experiences, referring to the potential of individual children and building activities that are fun and interesting for them. The teaching methods used include vocal exercises, namely breathing and vocalising, which are designed to ensure consistency and quality of voice, as well as the use of game and simulation techniques to visualize and understand the concept of tone. The research results show that this approach can improve children’s ability to express tones better